Rapid authentication of endangered Cistanche Herba (Rou Cong Rong) using a high-throughput multi-SNP panel and MALDI-TOF MS platform - Lei, Rong; Cao, Yixia; Yang, Yifen; Cong, Haolong; Li, Limei; Li, Xin; Shi, Junxia (Frontiers in Plant Science, 2026)
Cistanche Herba (Rou Cong Rong), a critically endangered edible tonic and medicinal plant, is traditionally valued for its nephroprotective and kidney-yang tonifying properties. However, wild populations are declining due to habitat loss, overharvesting, and increasing market demand, leading to widespread adulteration in commercial supplies. Conventional authentication methods, such as morphological examination, photochemical profiling, and ITS/ITS2 barcoding, often fail with processed materials due to DNA degradation. To overcome these limitations, we developed a high-throughput single-nucleotide polymorphism (SNP) genotyping platform that integrates multiplex PCR with MALDI-TOF mass spectrometry, targeting validated nuclear ITS and chloroplast-encoded ribosomal protein large subunit 16 (rpl16) loci. The assay utilizes four diagnostic SNPs specific to C. deserticola, allowing unambiguous differentiation from six adulterants. It demonstrates high sensitivity, detecting 0.07% genomic DNA (6.8 pg/μL) in mixed samples and 1% C. deserticola powder in dried tissue mixture. When validated on 27 dried specimens, the method showed 100% concordance with Sanger sequencing while reducing the total analysis time to approximately 10 hours. By overcoming the resolution limitations of traditional techniques, this approach provides a rapid and scalable solution to combat herbal substitution, support CITES compliance, ensure the integrity of functional foods and traditional medicines.